Industrial Training Report: The Office of Library and Knowledge Management Bachok Campus / Nor Farhana Mat Rozi - Mat Rozi, Nor Farhana (Faculty of Information Management, 2017)
Internship is one of the compulsory things for final year student of UniversitiTeknologi MARA (UiTM). As a student of Bachelor of Information Science (hons.) Library Management, I have to undertake the training during our semester 7 at the organization that is related with library management for five months period. The Office of Library and Knowledge Management, Universiti Malaysia Kelantan (UMK) Bachok Campus has been chosen as a place to do this industrial training which started from F1 August until 28th December 2017. This industrial training enables students to learn more detail about the process in the library especially in doing the technical process. Students will be placed in departmentsthat available in thelibrary to do the activities related to the departments. At UMK Library, I have been done my industrial training for four months at Bachok Campus and one month at City Campus. During my industrial training, I have gained so many things from the experience, skills, knowledge, information, lesson learned and more regarding to the library activities. This report consist the details about the background of the organization, the organization information of the departments, my industrial activities including the information regarding my special project for the organization.